ANALISIS KOMPETENSI MAHASISWA UNIVERSITAS NURUL HUDA DALAM PENYUSUNAN RUBRIKASI MAJALAH SEKOLAH DI ERA DIGITAL - Mila; Rosad, Ade; Lestari, Aminah; Susilowati, Yeni (Jurnal PENEROKA, 2026)
his research aims to describe and analyze the competency levels of Universitas Nurul Huda (UNUHA) students in developing digital-based school magazine rubrics. The focus of the study includes the students' ability to map content variations, craft communicative narratives, and master multimodal design technology. The scope of this research is limited to the analysis of various rubric types, such as school news, inspirational figure profiles, extracurricular activities, and school administrative services. The research method employed is a descriptive qualitative approach using content analysis techniques to provide an in-depth overview of the phenomenon being studied. Data were collected through visual documentation techniques and observation notes of the students' digital works. The results indicate that the students possess excellent competence in developing digital magazine rubrics. This is evidenced by their ability to systematically apply the 5W+1H elements in news rubrics, as well as their sensitivity in selecting relevant profile subjects. Furthermore, students are able to integrate inclusive content—such as scholarship information and New Student Admissions (PPDB)—with interactive multimodal layouts using the Canva application. A compelling finding of this research is the students' ability to create news through inspirational narratives and aesthetic visual elements, ensuring that the digital magazine functions not only as an information medium but also as an adaptive educational tool in the digital era.